一种仿生推进装置研究 - 张晓涛; 吕建刚; 郭劭琰; 宋彬; 腾飞 (Jixie chuandong)
A kind of bionic propulsion unit is proposed by the research on the swimming stroke of jellyfish.The unit in order to achieve bionic propulsion of large stroke reciprocating motion uses slider-crank mechanism to drive serial mechanism of scissor-like element.The rationality of mechanism design and correctness of function realization is verified by modeling and motion simulation of virtual prototype.At last,a principle prototype is made and tested in laboratory conditions.